FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - Jervis Jervis; Purnamawati Helen Widjaja; Verawati Verawati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research was conducted with the aim of finding empirical evidence regarding the effects of profitability, leverage, firm size and institusional ownership toward tax avoidance in energi sector companies listed on the IDX (Indonesian Stock Exchange). The observation period is during 2017-2021. This research used 76 samples obtained using purposive sampling method. The data that has been obtained is then processed using the Microsoft Excel 2019 and SPSS version 26.It is shown that from this research, that the independent variable leverage significantly affects the tax avoidance positively. However institusional ownership significantly affects the tax avoidance negatively. Both profitability and firm size have no affect on tax avoidance.